iLEINITIATIVE: Interactive Online Platform In Teaching and Learning Arabic For Gifted Students - Abdel Rahman Ibrahim Suleiman Islieh; Nurkhamimi Zainuddin; Wan Ahmad Zakry Wan Kamaruddin; Zulkarnin Zakaria; Mohd Rushdan Mohd Jailani (Science and Engineering Research Support Society, 2024)
International Journal of Advanced Science and Technology Vol. 29, No. 6s, (2020), pp. 1317-1328